2019
DOI: 10.1186/s42480-019-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas separation by a MOF with one-dimensional channels

Abstract: Noble gas separation by microporous materials is a promising alternative to energy-intensive cryogenic distillation method by reducing the separation cost; however, developing novel microporous materials with excellent noble gas separation performance is still challenging due to closing chemical and physical properties among the gases. In this study, we propose to separate the noble gases (He, Ne, Ar, Kr and Xe) utilizing a metal organic framework (MOF), named SIFSIX-3-Zn, with ultra-micron sized 1-dimenssiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…The largest Xe atoms ( σ =3.95 Å) apparently do not diffuse through the interchannel apertures at all due to large size. In such case, the obtained intrachannel activation barriers increase in accordance with their larger kinetic diameters in a series Ar < Kr < Xe, being common upon adsorption by other porous materials, see Figure S13 [45, 46] …”
Section: Figuresupporting
confidence: 54%
See 1 more Smart Citation
“…The largest Xe atoms ( σ =3.95 Å) apparently do not diffuse through the interchannel apertures at all due to large size. In such case, the obtained intrachannel activation barriers increase in accordance with their larger kinetic diameters in a series Ar < Kr < Xe, being common upon adsorption by other porous materials, see Figure S13 [45, 46] …”
Section: Figuresupporting
confidence: 54%
“…In such case, the obtained intrachannel activation barriers increase in accordance with their larger kinetic diameters in a series Ar < Kr < Xe, being common upon adsorption by other porous materials, see Figure S13. [45,46] The understanding of adsorption mechanisms and their corresponding energetic characteristics is of high importance for predictions of the adsorption selectivity. Particularly, the evaluation of structure-and guest-defined activation barriers in dynamic materials may explain such phenomena as selectivity of adsorption-induced phase transitions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…13−15 The highthroughput computational screening suggested that MOFs possessing tube-like pore systems with cavity diameters (slightly larger than the size of Xe) and abundant polar functionalities are the most advantageous candidates for efficient Xe/Kr separation, 16 as exemplified by squarate-1a, 17 SBMOF-20, 30 and SiFSiX-3-Zn. 34 Herein, we report robust ultramicroporous (pore size below 0.7 nm) MIL-120 with ordered one-dimensional (1D) pore channels (5.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption separation technology employing highly selective solid adsorbents is regarded as a promising approach for various gas-mixture separations. , Given the similar kinetic diameters (4.047 vs 3.655 Å for Xe and Kr) and polarizability (40.4 × 10 25 vs 24.8 × 10 25 cm –3 for Xe and Kr), advanced porous adsorbents are imperatively required. Metal–organic frameworks (MOFs) have shown versatile modulation over aperture size, pore environment, and reticular geometry, thus exhibiting outstanding performances in gas-mixture separation and trace impurity removal. The high-throughput computational screening suggested that MOFs possessing tube-like pore systems with cavity diameters (slightly larger than the size of Xe) and abundant polar functionalities are the most advantageous candidates for efficient Xe/Kr separation, as exemplified by squarate-1a, SBMOF-20, and SiFSiX-3-Zn …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the price of high-purity Xe and Kr is ∼$5000 per kilogram . At present, the dominated technique to produce noble gases in industry is cryogenic distillation, which is based on the differences in boiling points of various gases (27 K for Ne, 87 K for Ar, 120 K for Kr, and 165 K for Xe). , In this process, air was liquefied first and then fractionally distillated in columns with different temperatures to obtain various gases such as N 2 , Ar, Kr, and Xe. Despite this, Kr and Xe of high purity cannot be directly obtained but contain a 20/80 (v/v) mixture of Xe/Kr and Ar contaminate. , Meanwhile, this process is an energy-intensive and costly process.…”
Section: Introductionmentioning
confidence: 99%